1998
DOI: 10.1006/viro.1998.9097
|View full text |Cite
|
Sign up to set email alerts
|

Autographa californicaNucleopolyhedrovirus Infection Results in Sf9 Cell Cycle Arrest at G2/M Phase

Abstract: Baculovirus infection results in the induction of membrane structures within the nucleoplasm of the host cells. The source of these membranes is unclear; however, using the normal dynamics of cellular membranes and the nuclear envelope as a model, it is possible that the cell cycle might play a role in the regulation of formation of these intranuclear membranes. Therefore, one goal of this study was to investigate the effect of baculovirus infection on the cell cycle of Sf9 host cells. Since few data are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 45 publications
9
86
0
1
Order By: Relevance
“…There have been various studies reporting perturbations in cell cycle and apoptotic mechanisms after baculovirus infection. In one study, AcMNPV was observed to arrest the Sf9 cell cycle at the G 2 /M stage (Braunagel et al, 1998) whilst in another study, synchronized Sf9 cells when infected at the G 1 or S phase were arrested in the S phase, whilst those infected at the G 2 /M stage were blocked at the G 2 /M stage (Ikeda & Kobayashi, 1999). In yet another study, Helicoverpa armigera nucleopolyhedrovirus was found to arrest cell growth at the G 2 /M stage (Zhou et al, 2004).…”
Section: Expression Profiling Of Spltnpv Mirnas At Different Time Intmentioning
confidence: 99%
“…There have been various studies reporting perturbations in cell cycle and apoptotic mechanisms after baculovirus infection. In one study, AcMNPV was observed to arrest the Sf9 cell cycle at the G 2 /M stage (Braunagel et al, 1998) whilst in another study, synchronized Sf9 cells when infected at the G 1 or S phase were arrested in the S phase, whilst those infected at the G 2 /M stage were blocked at the G 2 /M stage (Ikeda & Kobayashi, 1999). In yet another study, Helicoverpa armigera nucleopolyhedrovirus was found to arrest cell growth at the G 2 /M stage (Zhou et al, 2004).…”
Section: Expression Profiling Of Spltnpv Mirnas At Different Time Intmentioning
confidence: 99%
“…of 10. Our employment of an asynchronous culture for this experiment may have been the cause of the observed variation (Braunagel et al, 1998;Ikeda & Kobayashi, 1999). Typically, a stationary (preexpansion) phase of the bright IE1-associated structures required 2-3 h, after which the IE1-associated structures began to expand.…”
Section: Time-lapse Imaging Of Ie1-gfp During Viral Infection Demonstmentioning
confidence: 99%
“…A gradual release of the arrested cells from the 'nocodazole barrier' occurred, allowing cells to complete mitosis, recover and grow similarly to untreated cells. The recovery of nocodazole-treated cells lasted several hours (Braunagel et al, 1998) with the appearance of the first cell divisions only 6 hours after washing off the nocodazole (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…Nocodazole (10 碌g/ml) (Braunagel et al, 1998) was added to the cells 24 hours after culture dilution. The response to Cry1C was evaluated 24 to 48 hours after nocodazole addition.…”
Section: Cell Synchronizationmentioning
confidence: 99%